Flexible Confinement and Manipulation of Mie Resonances via Nano Rectangular Hollow Metasurfaces. Issue 13 (18th April 2022) - Li, Zhancheng; Geng, Guangzhou; Cheng, Jiaqi; Liu, Wenwei; Yu, Shiwang; Xie, Boyang; Cheng, Hua; Li, Junjie; Zhou, Wenyuan; Tian, Jianguo; Chen, Shuqi
Abstract: Mie resonances excited in high‐index all‐dielectric metasurfaces provide a powerful platform for the constraint and manipulation of light at the subwavelength scale, which enable tremendous advanced developments in optical field manipulation, imaging, and sensing. Recently, how to manipulate and confine Mie resonances in the frequency domain has attracted tremendous interest since it is invaluable for the implementation of frequency‐selective and ‐multiplexed optical devices. Here, the authors theoretically analyze and experimentally demonstrate that the nano rectangular hollow (NRH) metasurfaces are promising candidates for the flexible confinement and effective manipulation of Mie resonances in the frequency domain. They reveal that the diameter of the hollow in the NRH can provide an efficient degree of freedom for the constraint of displace currents in the space domain, which results in the confinement of Mie resonances in the frequency domain. The excitation wavelength of the Mie resonance can also be manipulated by adjusting the side length of the NRH. The potential uses of NRH metasurfaces in the implementation of frequency‐selective intensity encoding and optical encryption are theoretically and experimentally demonstrated. The results provide a fertile ground for confining Mie resonances in the frequency domain and can be further applied in frequency‐multiplexed optical devices. Abstract : Nano rectangular hollow metasurfaces are theoretically and experimentally demonstrated as a powerful platform for flexible confinement and efficient manipulation of Mie resonances in the frequency domain. With devisable resonant wavelength and bandwidth, their potential application value in frequency‐selective intensity manipulation and optical encryption has been experimentally validated.